TABUIK: LOCAL WISDOM AS AN ALTERNATIVE FOR SUPPRESSING THE IMPACT OF STRUCTURAL CHANGE IN PARIAMAN - Zainal Fadri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2019)
Arthur Lewis's structural change theory focused on the development shows the process of change which occurs from the traditional economic society towards the industrial economic society. The development of traditional economies in the countryside into the industrial economy in urban areas has a serious impact on equitable distribution of ongoing economic development. The villagers initially worked in the agricultural sector moved to the city then due to an absorption of labor in the industrial sector. Massive urbanization is a serious impact caused by this change, so that there is a vacant labor force in the countryside and an increase in unemployment in urban areas. The problem caused by structural changes in economic development can be overcome by the local wisdom approach of the local community. In this paper, the case is taken in Pariaman community especially the Tabuik ceremony as an annual routine. Tabuik in Pariaman requires that the community remaining in Pariaman and undergo a routine as an agricultural community because there are many special needs and rituals requiring ceremonial materials from the agricultural field. The local wisdom of people in Pariaman is not involved in significant urbanization cases. Tabuik as a control the flow of globalization makes the community and economic activities manageable as of the development in Pariaman with traditional agricultural economic models and adequate labor naturally.